Ministry of Finance Decree No. 289 of the year 2021 On Amending Certain Provisions of the Executive Regulations of the Law Organizing the Contracts Concluded by Public Entities As Issued by Minister of Finance Decree No. 692/2019 = وزارة المالية قرار رقم 289 لسنة 2021 بتعديل بعض أحكام اللائحة التنفيذية لقانون تنظيم التعاقدات التى تبرمها الجهات العامة الصادرة بقرار وزير المالية رقم 692 لسنة 2019 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic